INFLUENCE OF THE TYPE OF CRITERIA USED FOR CLASSIFICATION OF THE BEST STUDIES IN MEDICAL EVENTS - Vieiria, René Aloisio da Costa; Paulinelli, Regis Resente; Rodrigues, Fábio Francisco Oliveira; Moreira, arise Amaral Rebouças; Caponero, Ricardo; Rahal, Rosemar Macedo Sousa; Facina, Gil; Freitas Junior, Ruffo de (Mastology, 2026)
Objective: The aim of this study was to evaluate the impact of the study methodology and the type of evaluation in the selection of studies for presentation of Scientific Events. Methods: This is a prospective, observational, transversal study, applied in a cohort of studies submitted for presentation at BBCS 2021. This study does not require CEP evaluation by resolution 466/2012. All BBCS 2021 Evaluating Committee members were invited to participate in the study. The studies were presented blindly to the evaluators, with three forms of evaluation being presented. The first criterion was based on six criteria (method, ethics, design, originality, promotion, and social contributions), representing the pattern of the event. In the second criterion, the evaluator considered a grade from 0 to 10 for the study. The third criterion was based on five criteria (presentation, method, originality, scientific, and social contributions). The results were grouped and the studies classified. For evaluation of the correlation of the criteria of the items, the Cronbach’s alpha was performed. A factorial analysis was performed. For evaluation of the median differences between the tests, we used Kruskal-Wallis and post hoc Dunn’s tests. To evaluate the difference in the study classifications, we used the Friedman test and Namenyi’s All-Pairs Comparisons. The “R” and IBM SPPS Statistics were used for the analysis. Results: In all, 122 studies were evaluated, of which 94 were original studies and 28 were case reports. Five professors performed all the evaluations. Original studies had better scores. There was a good correlation with the items of criteria 1 (α=0.730) and 3 (α=0.937). The methodology and study design showed the main criteria needed for study evaluation. The Kruskal-Wallis showed differences in the results (p<0.001) of all criteria used [1–2 (p<0.001); 1–3 (p<0.001); 2–3 (p=0.004)]. The Friedman test showed a difference in the ranking of the studies (p<0.001), for all studies (p<0.01). Conclusion: Methodologies that use many criteria showed good correlation. Methodology and study design represent the main criteria. The methodology used in the evaluation of studies influences the ranking of the best studies.